Picosecond infrared probing of the vibrational spectra of transients formed upon UV excitation of stacked G-tetrad structures - KELLY, JOHN MOFFAT (My University, 2007)
The photophysical properties of stacked G-tetrads in diverse systems, including concentrated solutions of 59-guanosine monophosphate (59-GMP), polyguanylic acid (poly(G)) and the G-rich oligodeoxynucleotide sequence characteristic of human telomericDNA, are probed by ps-TRIR and compared to those of the monomeric 59-GMP.
PUBLISHED
Keywords: (59-GMP); (59-GMP)